Impact of pulpotomy versus root canal treatment on oral health-related quality of life in patients with pulpitis: a systematic review - Syeda Abeerah Tanveer; Itrat Batool; Robia Ghafoor (Journal of the Pakistan Medical Association, 2026)
Objective: The aim of the review is to compare the pain outcome measures and oral health-related quality of life (OHRQOL) in pulpotomy versus root canal treatment. Methodolgy: The systematic review was conducted from October 10 to November 21, 2024, and comprised literature search on electronic databases: PubMed (CENTRAL, MEDLINE) and Cochrane Central Register of Controlled Trials (CENTRAL) [Cochrane Library], Clarivate Analytics' Web of Science (including Web of Science Core Collection—WoS, Russian Science Citation Index—RSCI, SciELO Citation Index—SCIELO), and CINAHL using key words and Boolean operators, including “pulpotomy” OR “pulpotomies” OR “pulp capping” AND “root canal treatment” OR “root canal therapy” OR “pulpectomy” OR “pulpectomies” AND “pulpitis” AND “quality of life” OR “oral health” AND “permanent dentition” OR “secondary” in the electronic databases. The outcomes evaluated were postoperative pain after full pulpotomy compared to non-surgical root canal therapy as well as their quality of life at different time intervals. Results: The initial search retrieved 729 articles from electronic databases of them 5 articles were included. Among the included studies, three (60%) demonstrated a low risk of bias, while two (40%) were assessed as having a high risk of bias. Conclusion: Pulpotomy may be as effective as root canal treatment in managing postoperative pain, while quality of life assessment showed significant improvement over time in favour of pulpotomy. Keywords: Pulpotomy, Root canal treatment, Pulpitis, Quality of life, Pulp capping. PROSPERO Registration: PROSPERO 2024 Available from: https://www.crd.york.ac.uk/PROSPERO/view/ CRD42024622436